2021
DOI: 10.21203/rs.3.rs-178316/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Biogenic Green Synthesis of Nanoparticles from Living sources with Special Emphasis on Their Biomedical Applications

Abstract: Nanobiotechnology has been achieved great significance in terms of nanomedicine & many others. But the first challenge in nanobiotechnology science is the preparation of stable nanoparticles. Presently, many preparation methods have been developed like different chemical & physical processes, but the main drawbacks of these processes are required hazardous chemicals, environmental impact, and ultimately expenses a lot. To overcome these challenges another advanced technology has been developed, which i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 84 publications
0
3
0
Order By: Relevance
“…By modifying the surface of silver nanoparticles, their cytotoxicity can be reduced by reducing the contact surface with cells. Also, in subsequent studies, researchers found that silver nanostructures can enter cells and affect DNA by releasing silver cations (Rather et al, 2021). In this regard, it has been determined that the antibacterial activity of silver nanostructures depends on the amount of silver cations released (Rather et al, 2021).…”
Section: Use Of Nanostructuresmentioning
confidence: 99%
See 2 more Smart Citations
“…By modifying the surface of silver nanoparticles, their cytotoxicity can be reduced by reducing the contact surface with cells. Also, in subsequent studies, researchers found that silver nanostructures can enter cells and affect DNA by releasing silver cations (Rather et al, 2021). In this regard, it has been determined that the antibacterial activity of silver nanostructures depends on the amount of silver cations released (Rather et al, 2021).…”
Section: Use Of Nanostructuresmentioning
confidence: 99%
“…Also, in subsequent studies, researchers found that silver nanostructures can enter cells and affect DNA by releasing silver cations (Rather et al, 2021). In this regard, it has been determined that the antibacterial activity of silver nanostructures depends on the amount of silver cations released (Rather et al, 2021). In general, by reducing the size of silver nanostructure, its antibacterial effect increases due to the increase in the concentration of released Ag + ions (Rather et al, 2021).…”
Section: Use Of Nanostructuresmentioning
confidence: 99%
See 1 more Smart Citation